خصائص السنن الإلهية في المنظور القرآني - سلطان، حيدر حميد; شكراني، رضا; لطفي، سيد مهدي (د محمد أمين الضناوي, 2024)
إن موضوع السنن من الحقائق المهمة الموجودة في القرآن الكريم، التي جعلها الله قانونا ساريا على مخلوقاته جميعها، من دون تخلف ولا تبدل ولا محاباة لأحد، وقد جرت قدرته تعالى على جعل هذه السنن حاكمة على الكون بأسره؛ لتنظم لنا الحياة وتذلل صعوباتها، والجدير بالذكر أن هذه السنن لا تختلف ولا تتخلف، ولا تجامل ولا تحابي، فهي عادلة، وتسري على المجتمعات كافة، فحياة البشرية على هذه المعمورة محكومة ومقننة بقوانين، لا يمكن أن تتغير فهي ثابتة ومطردة؛ ليتنبه الإنسان إلى أهميتها، وضرورة الأخذ بقوانينها؛ لتحصيل مراده المطلوب، وهنا تكمن أهميتها في منظور الفكر البشري، ومع أهميتها تلك وتأكيد القرآن الكريم الأخذ بها، وعدم إهمالها، فإنها لم تحظ بالدراسة الكافية، وهي مختصرة بعدد قليل من الدراسات التي لم تستوعب هذه الحقيقة القرآنية المهمة والتي تكون منطلقا لبقية العلوم الإنسانية والاجتماعية؛ وتكمن أهمية هذه الدراسة في إبراز بعض خصائص السنن الإلهية ومدى تأثيرها على الأمم من الناحيتين الإيجابية والسلبية، فكان لزاما علينا تأكيد هذا الموضوع وإبراز أهميته من خلال التعرف إلى هذه السنن الإلهية، ومدى تأثيرها على هذه الأمة؛ ليتبين انحرافها عن المنهج السماوي، وتسلط عليها الأمم التي تسير بهم إلى الهوان، والتضعيف، ونهب خيراتهم، وجعلتهم يرون في الإسلام عائقا أمام تقدمهم، وليتبين لنا أن الانحراف عن المنهج السماوي، سيؤدي حتما إلى تدهور أحوال الأمم واندثار الحضارات، وقد كشفت هذه الدراسة أن مفهوم السنن الإلهية له معنى واحد يختصر المعاني المتقاربة جميعها والتي ذكرت سابقا، وهو دلالتها على توالي الفعل واطراده على نهج واحد، وبينت أن بعض الآراء التي أسهمت في تعداد خواصها، هو إسهاب مفرط، ورأى الباحث أن اختصار خصائصها التي لها المعنى نفسه والدلالة نفسها، تكمن فائدته في تبويب هذا العلم كما بقية العلوم الأخرى، فالنفاد وعدم التخلف هو الثبات. والحكمة والعدل: هما الربانية. وبعد أن جمعت التعريفات والأنواع التي اعتمدوها العلماء الذين كتبوا في السنن الإلهية كلا حسب فنه، لذا جاءت هذه الدراسة لتأكيد مفهوم السنن الإلهية، والتعرف إلى أهميتها وأنواعها، وخصائصها وتناولت بعض الشبهات وأجابت عليها لإزالة الغموض وجلاء فكرة وجود سنن الله في خلقه. The subject of divine laws (sunnah) is one of the most important truths found in the Holy Quran. God has made these laws applicable to all His creations, without deviation, change, or favoritism towards anyone. His divine power has established these laws to govern the entire universe, to organize our lives, and to ease its difficulties. It is noteworthy that these laws do not vary or deviate they are just and apply to all societies. Human life on this earth is governed and regulated by unchangeable and consistent laws, so that people can recognize their importance and the necessity of adhering to them to achieve their desired goals. Despite their significance and the Quran’s emphasis on adhering to them and not neglecting them, these laws have not been sufficiently studied. Only a few studies have briefly covered this important Quranic truth, which serves as a foundation for other human and social sciences. The importance of this study lies in highlighting some characteristics of the divine laws and their impact on nations, both positively and negatively. Thus, it is imperative to emphasize this subject and highlight its importance by understanding these divine laws and their impact on this nation, to reveal their deviation from the divine path, which leads to their subjugation by other nations, resulting in humiliation, weakening, and exploitation of their resources. These nations see Islam as an obstacle to their progress. It becomes evident that deviation from the divine path inevitably leads to the deterioration of nations and the collapse of civilizations. This study has revealed that the concept of divine laws has a singular meaning that encompasses all the previously mentioned similar meanings, indicating the continuity and consistency of actions in a uniform manner. It also showed that some opinions that elaborated on enumerating their characteristics were overly detailed. The researcher believes that summarizing these characteristics, which have the same meaning and indication, is beneficial for categorizing this science like other sciences. The constancy and nondeviation imply stability, and wisdom and justice imply divinity. After collecting the definitions and types used by scholars who wrote about divine laws, each according to their expertise, this study aims to reaffirm the concept of divine laws, recognize their importance, types, and characteristics, and address some misconceptions to clarify the idea of the existence of God›s laws in His creation.
Keywords: السنن الإلهية -- السنن الكونية -- التفسيرات القرآنية